Expulsion for Adultery Perpetrators Muhshan at Panyabungan: An Islamic Law Perspective - Rasyid, Arbanur (UIN Sunan Kalijaga, 2022)
Abstract: This article examines the practice of expelling perpetrators muhshan in the Panyabungan society, which normatively (Islamic law) should be punished by stoning. This phenomenon is fascinating to study because the Panyabungan people are Islamic followers who are very fanatical and have a strong religion. This article is based on field data supplemented by library data. Three fundamental issues are examined in this article, namely the process of enforcing customary law for adulterers muhshan in Panyabungan society, the argument for the application of expulsion punishment to adulterers' muhshan, and how Islamic law views the practice of expulsion in the case of adultery. Uses a normative and sociological approach this article finds the fact that the practice of expulsion of adulterers muhshan in Panyabungan is enforced if the perpetrator has been proven to have committed adultery. The practice of expelling the perpetrators of muhshan adultery is carried out for two reasons: following the traditions or customs that have been in effect and the impossibility of applying the stoning law in Indonesia. This article also finds evidence that the purpose of imposing the penalty of expulsion for adulterers muhshan in Panyabungan is to give a deterrent effect to the perpetrators of adultery and, at the same time as a preventive measure for people not to commit adultery. In addition, the punishment is also intended to maintain the excellent name and cleanliness of the village from disobedience acts. Abstrak: Artikel ini mengkaji praktik pengusiran terhadap pelaku zina muhshan dalam masyarakat Panyabungan yang secara normatif (hukum Islam) seharusnya diberi hukuman rajam. Fenomena ini sangat menarik untuk dikaji karena masyarakat Panyabungan pada dasarnya termasuk penganut Islam yang sangat fanatis dan kuat beragama. Artikel ini didasaran pada data-data lapangan yang dilengkapi dengan data-data kepustakaan. Ada tiga persoalan mendasar yang dikaji dalam artikel ini, yakni proses pemberlakuan hukum adat bagi pelaku zina muhshan pada masyarakat Panyabungan, argumen diterapkannya hukuman pengusiran terhadap pelaku zina muhshan, dan bagaimana hukum Islam memandang praktik hukuman pengusiran dalam kasus perzinahan tersebut. Menggunakan pendekatan normatif sosiologis, artikel ini menemukan fakta bahwa praktik pengusiran terhadap pelaku zina muhshan di Panyabungan diberlakukan apabila pelaku telah terbukti melakukan perzinahan. Praktik hukuman pengusiran terhadap pelaku zina muhshan tersebut dilakukan karena dua alasan, yakni mengikuti tradisi atau adat-istiadat yang telah berlaku dan tidak dimungkinkannya penerapan hukum rajam di Indonesia. Artikel ini juga menemukan bukti bahwa perapan hukuman pengusiran bagi pelaku zina muhshan di Panyabungan dimaksudkan untuk memberikan efek jera kepada para pelaku zina dan sekaligus sebagai upaya preventif bagi masyarakat supaya tidak melakukan perzinahan. Selain itu, hukuman tersebut juga dimaksudkan untuk menjaga nama baik dan kebersihan desa dari tindakan kemaksiatan.